Impact assessment of Controlled Mechanical Ventilation systems for air quality in school buildings: a study protocol (Epidemiology, Biostatistics, and Public Health, 2025)
Background: Indoor air is an important public health issue and the COVID-19 pandemic has highlighted even more the importance of indoor air quality in schools. One of the main measures to preserve good indoor air quality is to maintain adequate indoor air exchange, and energy-efficient mechanical ventilation has been shown to be effective in improving indoor air quality and health of the occupants.Methods: A pre-post study and trend analysis will be carried out. As the project involves the installation of Controlled Mechanical Ventilation (CMV) systems in schools, the primary aim of the study is to assess the perceived indoor air quality in classrooms in a population of primary and secondary school students without (pre-installation) and with (post-installation) CMVs. The secondary aim is the assessment of health outcomes, investigating the prevalence of dermatological, respiratory, ocular and general disorders reported before and after the intervention, and stratifying by sociodemographic variables. The evaluation of the effectiveness of CMV systems on air quality will be evaluated through chemical-physical and microbiological sampling after the installation of CMVs. The perceived air quality and health assessment will be performed through a survey, distributed before and after CMVs installation.Conclusions: The present study protocol aims to highlight the importance of indoor air quality for students and school personnel, as well as propose new strategies and measures to deal with this raising issue, enacting measures and systems that will be sustainable from an environmental, energetical, and acoustic point of view, while still ensuring the best possible health outcomes.
Keywords: indoor air quality; controlled mechanical ventilation; prevention; public health; school